ApoA‐I mutations, L202P and K131del, in HDL from heterozygotes with low HDL‐C. Issue 3 (12th February 2014) - Ljunggren, Stefan; Levels, Johannes H. M.; Turkina, Maria V.; Sundberg, Sofie; Bochem, Andrea E.; Hovingh, Kees; Holleboom, Adriaan G.; Lindahl, Mats; Kuivenhoven, Jan Albert; Karlsson, Helen; Semba, Richard D.; Enghild, Jan J.
<x xml:space="preserve">Abstract</x> Purpose Mutations in apolipoprotein A‐I (apoA‐I) may affect plasma high‐density lipoprotein (HDL) cholesterol levels and the risk for cardiovascular disease but little is known about the presence and effects of circulating apoA‐I variants. This study investigates whether the apoA‐I mutations, apoA‐IL202P and apoA‐IK131del, are present on plasma HDL particles derived from heterozygote carriers and whether this is associated to changes in HDL protein composition. Experimental design Plasma HDL of heterozygotes for either apoA‐IL202P or apoA‐IK131del and family controls was isolated using ultracentrifugation. HDL proteins were separated by 2DE and analyzed by MS. Results ApoA‐I peptides containing apoA‐IL202P or apoA‐IK131del were identified in HDL from heterozygotes. The apoA‐IL202P mutant peptide was less abundant than wild‐type peptide while the apoA‐IK131del mutant peptide was more abundant than wild‐type peptide in the heterozygotes. Two‐dimensional gel electrophoresis analyses indicated that, compared to controls, HDL in apoA‐IL202P carriers contained less apoE and more zinc‐α‐2‐glycoprotein while HDL from the apoA‐IK131del heterozygotes contained more alpha‐1‐antitrypsin and transthyretin. Conclusions and clinical relevance Both apoA‐IL202P and apoA‐IK131del were identified in HDL. In heterozygotes, these mutations have markedly differential effects on the concentration of wild‐type apoA‐I in the circulation, as well as the HDL proteome, both of which might affect the clinical phenotype encountered in the heterozygous carriers.